Variation of forage quality traits in Tunisian populations of Brachypodium hybridum in response to phosphorus deficiency. Issue 6 (9th October 2021) - Neji, Mohamed; Tlahig, Samir; Hessini, Kamel; Taamalli, Wael; Abdelly, Chedly; Kouas, Saber
Abstract: Natural populations of plants may express plastic response, evolve local adaptation, or combine both mechanisms to enhance their genetic variation. Here, 79 lines from Tunisian Brachypodium hybridum populations were cultivated in two contrasting phosphorus (P) availability levels, and their genetic variation was investigated using forage quality traits to identify the mechanisms governing their genetic variation. Results revealed large variation among populations for most traits and separation between coastal and inland populations in both P levels. All traits revealed high heritability, and the response of most traits to P deficiency was influenced by the population effect which accounted 52.38% of the variation, indicating strong population differentiation. Although significant for most traits, only 18.13% of variation was attributed to P treatment, suggesting little plastic response to P deficiency. However, the lack of population × treatment effect for most traits suggested a common plastic response in populations. Moreover, 56.99% of variation was attributed to environmental factors with distance to coastline, precipitation seasonality, and annual precipitation being the major factors, suggesting that the strong population differentiation reflects local adaptation to specific environments. Contrary to coastal populations characterized by high levels of fiber‐related traits, the inland ones displayed high values of most energy‐related traits, suggesting that these latter were characterized by higher forage quality. Overall, our results suggested that the effect of local adaptation overrides the effect of phenotypic plasticity regarding the variation of forage quality traits, indicating a broad adaptive genetic differentiation among the populations of B. hybridum in response to P deficiency. Core Ideas: The variation of forage quality in response to P deficiency in B. hybridum populations was analyzed. Significant population and P treatment effects in response to P deficiency were detected. Results showed broad adaptive genetic differentiation in forage quality traits. The variation of forage quality under phosphorus deficiency influenced by environment. The coastal‐inland differentiation points toward local adaptation of populations.